Integrative analyses indicate an association between ITIH3 polymorphisms with autism spectrum disorder - Xie, Xinyan (Sci Rep, 2020)
It is challenge to pinpoint the functional variants among numerous genetic variants. Investigating the spatial dynamics of the human brain transcriptome for genes and exploring the expression quantitative trait loci data may provide the potential direction to identify the functional variants among autism spectrum disorders (ASD) patients. In order to explore the association of ITIH3 with ASD, the present study included three components: identifying the spatial-temporal expression of ITIH3 in the developing human brain using the expression data from the Allen Institute for Brain Science; examining the cis-acting regulatory effect of SNPs on the ITIH3 expression using UK Brain Expression Consortium database; validating the effect of identified SNPs using a case-control study with samples of 602 cases and 604 controls. The public expression data showed that ITIH3 may have a role in the development of human brain and suggested a cis-eQTL effect for rs2535629 and rs3617 on ITIH3 in the hippocampus. Genetic analysis of the above two SNPs suggested that the over-dominant model of rs2535629 was significantly associated with decreased risk of ASD. Convergent lines of evidence supported ITIH3 rs25352629 as a susceptibility variant for ASD.